Yeast Monitoring of Wine Mixed or Sequential Fermentations Made by Native Strains from D.O. “Vinos de Madrid” Using Real-Time Quantitative PCR - García, Margarita; Esteve-Zarzoso, Braulio; Crespo, Julia; Cabellos, Juan M.; Arroyo, Teresa (Frontiers in Microbiology, 2017)
There is an increasing trend towards understanding the impact of non-Saccharomyces yeasts on the winemaking process. Although Saccharomyces cerevisiae is the predominant species at the end of fermentation, it has been recognized that the presence of non-Saccharomyces species during alcoholic fermentation can produce an improvement in the quality and complexity of the final wines. A previous work was developed for selecting the best combinations between S. cerevisiae and five non-Saccharomyces (Torulaspora delbrueckii, Schizosaccharomyces pombe, Candida stellata, Metschnikowia pulcherrima and Lachancea thermotolorans) native yeast strains from D.O. “Vinos de Madrid” at the laboratory scale. The best inoculation strategies between S. cerevisiae and non-Saccharomyces strains were chosen to analyze, by real-time quantitative PCR (qPCR) combined with the use of specific primers, the dynamics of inoculated populations throughout the fermentation process at the pilot scale using the Malvar white grape variety. The efficiency of the qPCR system was verified independently of the samples matrix, founding the inoculated yeast species throughout alcoholic fermentation. Finally, we can validate the positive effect of selected co-cultures in the Malvar wine quality, highlighting the sequential cultures of T. delbrueckii CLI 918/S. cerevisiae CLI 889 and C. stellata CLI 920/S. cerevisiae CLI 889 and, mixed and sequential cultures of L. thermotolerans 9-6C combined with S. cerevisiae CLI 889.